2002
DOI: 10.1007/s00422-002-0352-z
|View full text |Cite
|
Sign up to set email alerts
|

Cortical network reorganization guided by sensory input features

Abstract: Sensory experience alters the functional organization of cortical networks. Previous studies using behavioral training motivated by aversive or rewarding stimuli have demonstrated that cortical plasticity is specific to salient inputs in the sensory environment. Sensory experience associated with electrical activation of the basal forebrain (BasF) generates similar input specific plasticity. By directly engaging plasticity mechanisms and avoiding extensive behavioral training, BasF stimulation makes it possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 103 publications
(121 reference statements)
1
33
0
Order By: Relevance
“…However, these studies once again demonstrate that the adult auditory cortex remains plastic for attended, rewarded stimuli. It has been suggested that the interaction of auditory inputs, neuromodulator release, and top-down influences from higher auditory areas contribute to this learningbased cortical plasticity (20,(47)(48)(49)(50)(51)(52)(53)(54)(55). The fact that passive exposure to the same stimuli, when not reliably coupled to reward, has no measurable effect on frequency selectivity and tonotopicity of A1 in the present study again supports the conclusion that top-down modulation contributes significantly to learning-induced cortical plasticity in the adult brain (20).…”
Section: Discussionsupporting
confidence: 85%
“…However, these studies once again demonstrate that the adult auditory cortex remains plastic for attended, rewarded stimuli. It has been suggested that the interaction of auditory inputs, neuromodulator release, and top-down influences from higher auditory areas contribute to this learningbased cortical plasticity (20,(47)(48)(49)(50)(51)(52)(53)(54)(55). The fact that passive exposure to the same stimuli, when not reliably coupled to reward, has no measurable effect on frequency selectivity and tonotopicity of A1 in the present study again supports the conclusion that top-down modulation contributes significantly to learning-induced cortical plasticity in the adult brain (20).…”
Section: Discussionsupporting
confidence: 85%
“…ditioning or neuromodulatory pairing might also be influenced by top-down mechanisms (for review, see Kilgard et al, 2002;Suga and Ma, 2003;Weinberger, 2004). Ultimately, procedures that characterize plasticity using real-time awake recording methods might reveal top-down mechanisms that allow the cortex to switch between different flexible states of information processing according to rapidly changing environmental demands (Edeline et al, 1993;Ohl and Scheich, 1997;Ohl et al, 2001;Fritz et al, 2003Fritz et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Task-dependent influences on receptive fields in the primary sensory cortex have only been observed in awake animals and, even then, have only been observed to last for short periods of time. Studies that investigate long-term effects of conditioning on adult cortical map and/or their constituent receptive field organization have generally claimed that receptive field plas-ticity reflects the pattern of bottom-up sensory inputs and their relationship to reinforcement-based neuromodulator release (Ji et al, 2001;Kilgard et al, 2001Kilgard et al, , 2002Weinberger, 2004;Yan and Zhang, 2005). Our understanding of the relative contribution of bottom-up and top-down signals to adult cortical plasticity has remained clouded, however, because nearly every conditioning study has imposed varying attentional demands on subjects presented with varying sensory inputs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, learning on the network level is in large parts dependent on subjectively connoted sensory stimulation (i.e. salient cues) [56, 124]. Nonetheless, several studies have highlighted the positive effects of simple focused repetitive training [125, 126], though not all with positive results [127].…”
Section: Effects Of Stroke Rehabilitation In Humansmentioning
confidence: 99%